Moth smoke - Hamid, Mohsin, 1971- (New York : Farrar, Straus, and Giroux, 2000)
"When Darashikoh Shezad gets himself fired from his banking job in Lahore, he begins a decline that plummets the length of this sharply drawn, subversive tale. Before long, he can't pay his bills, and along with his electricity be loses his toehold among Pakistan's cell-phone-toting elite. As the jet set parties on behind high walls, Daru descends into drugs and dissolution.
For good measure, he falls in love with the wife of his childhood friend and rival, Ozi - beautiful, restless Mumtaz, to whom he is drawn with the obsessive intensity of a moth circling a candle flame.".
"Desperate to reverse his fortunes, Daru embarks on a career in crime, taking as his partner Murad Badehah, the notorious rickshaw driver, populist, and pirate. When a long-planned heist goes awry, Daru finds himself on trial for a murder he may or may not have committed. The uncertainty of his fate mirrors that of his country, hyped on the prospect of becoming a nuclear player even as corruption drains its political will."--BOOK JACKET.
Keywords: Young men -- Pakistan -- Fiction; Detective and mystery stories; Pakistan -- Social life and customs -- Fiction; Adventure stories; Love stories